Characterization of patients with cerebrovascular accident admitted to a primary care hospital in Chile - Sepúlveda-Contreras, Jorge (Universidad y Salud, 2020)
Introduction: Cerebrovascular accidents constitute a critical public health problem, whose major risk factors are hypertension, tobacco use and diabetes, among others. Objective: To characterize patients admitted with a diagnosis of cerebrovascular accident to the San Luis de Buin-Paine Hospital, which is a primary care institution belonging to the Southern Metropolitan Health Service of Chile. Materials and methods: An observational, descriptive and cross-sectional research was carried out with patients who were hospitalized in the rehabilitation unit with a diagnosis of ischemic or hemorrhagic cerebrovascular accident. A review of each electronic record was carried out with a sample containing 135 patients. Absolute frequencies and percentages were used for statistical processing of the data. Results: Ischemic stroke was observed in 85.92% of patients, with a significant percentage increase in the population over 51 years of age. The most frequent risk factors were high blood pressure and diabetes mellitus. The most common profession or trade was retiree (27.4%). Conclusions: This work found similar results to those reported by previous studies. Prevention of cerebrovascular diseases is associated with the maintenance of healthy habits and lifestyles that prevent the appearance of modifiable risk factors.